GORASP2/GRASP55 collaborates with the PtdIns3K UVRAG complex to facilitate autophagosome-lysosome fusion. Issue 10 (3rd October 2019) - Zhang, Xiaoyan; Wang, Leibin; Ireland, Stephen C.; Ahat, Erpan; Li, Jie; Bekier, Michael E.; Zhang, Zhihai; Wang, Yanzhuang
ABSTRACT: It has been indicated that the Golgi apparatus contributes to autophagy, but how it is involved in autophagosome formation and maturation is not well understood. Here we show that amino acid starvation causes trans -Golgi derived membrane fragments to colocalize with autophagosomes. Depletion of the Golgi stacking protein GORASP2/GRASP55, but not GORASP1/GRASP65, increases both MAP1LC3 (LC3)-II and SQSTM1/p62 levels. We demonstrate that GORASP2 facilitates autophagosome-lysosome fusion by physically linking autophagosomes and lysosomes through the interactions with LC3 on autophagosomes and LAMP2 on late endosomes/lysosomes. Furthermore, we provide evidence that GORASP2 interacts with BECN1 to facilitate the assembly and membrane association of the phosphatidylinositol 3-kinase (PtdIns3K) UVRAG complex. These findings indicate that GORASP2 plays an important role in autophagosome maturation during amino acid starvation. Abbreviations: ATG14: autophagy related 14; BafA1: bafilomycin A1 ; BSA: bovine serum albumin; CQ: chloroquine; EBSS: earle's balanced salt solution; EM: electron microscopy; EEA1: early endosome antigen 1; GFP: green fluorescent protein; GORASP1/GRASP65: golgi reassembly stacking protein 1; GORASP2/GRASP55: golgi reassembly stacking protein 2; LAMP1: lysosomal-associated membrane protein 1; LAMP2: lysosomal-associated membrane protein 2; MAP1LC3: microtubule associated protein 1 light chain 3; MTOR: mechanistic target of rapamycin kinase; PBS: phosphate-buffered saline; PtdIns3K: phosphatidylinositol 3-kinase; PtdIns3P: phosphatidylinositol 3-phosphate; PK: protease K; PNS: post-nuclear supernatant; RFP: red fluorescent protein; SD: standard deviation; TGN: trans-Golgi network; UVRAG: UV radiation resistance associated.